Physiologic specialization of Puccinia triticina in Andalusia (Spain) in 2004 and 2005 - Del Olmo A.I.; Sillero J.C.; Rubiales D. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Knowledge of the virulence spectrum of leaf rust is needed for a rational selection of resistance genes to be incorporated in commercial cultivars. In the present work we intend to determine the virulence of Andalusian isolates collected on durum wheats in years 2004 and 2005. Ten virulence phenotypes were found. All analysed isolates were virulent on Lr10, 12, 14a, 14b, 18 and 23 and avirulent on Lr1, 2a, 3, 3bg, 3ka, 9, 15, 17, 24 and 26. The most common virulence phenotype was BBBPPM which was spread all over the surveyed area. A decrease on virulence on Lr1, 3, 3bg, 15, 17, 26 and 28 were observed in 2004 and 2005 when compared to 2003.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)